Printable Photovoltaics: A Versatile Self‐Organization Printing Method for Simplified Tandem Organic Photovoltaics (Adv. Funct. Mater. 21/2016). (6th June 2016) - Kim, Seok; Kang, Hongkyu; Hong, Soonil; Lee, Jinho; Lee, Seongyu; Park, Byoungwook; Kim, Junghwan; Lee, Kwanghee
Abstract : A versatile self‐organization printing technique for fabricating efficient and simplified tandem organic photovoltaics is demonstrated on page 3563 by H. Kang, K. Lee, and co‐workers, using a nanocomposite of interfacial and photoactive materials. By adjusting the molecular weight of the interfacial material, a spontaneous vertical self‐organization is successfully achieved through printing processes.